Reorientasi tujuan dan peranan undang-undang dalam masyarakat multi budaya: perspektif antropologi undang-undang - Inyoman Nurjaya (Fakulti Undang - Undang, 2005)

(untitled)
Indonesia is well known as a multicultural country in terms of ethnic, religion, racial and social stratification. Therefore, Unity in Diversity is reflected as an official motto of the State in order to describe the empirical social and cultural diversity of Indonesia. This multicultural condition brings about the consequence that role and function of the state law that established and enforced by the government should also be reviewed and reoriented with the purpose of enhancing legal and social justice particularly for the life of folk law in the country. This article attempts to analyze this empirical legal condition especially in term of main goal, role and function of the law in the multicultural society of Indonesia by using legal anthropology approach